2021
DOI: 10.3390/ijms22094617
|View full text |Cite
|
Sign up to set email alerts
|

When the Balance Tips: Dysregulation of Mitochondrial Dynamics as a Culprit in Disease

Abstract: Mitochondria are dynamic organelles, the morphology of which is tightly linked to their functions. The interplay between the coordinated events of fusion and fission that are collectively described as mitochondrial dynamics regulates mitochondrial morphology and adjusts mitochondrial function. Over the last few years, accruing evidence established a connection between dysregulated mitochondrial dynamics and disease development and progression. Defects in key components of the machinery mediating mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…Studies have shown that the continuous fission and fusion of mitochondria are important for maintaining mitochondrial morphology and function ( Kyriakoudi et al, 2021 ). Mammals contain two mitofusins, namely mitofusin (Mfn)-1 and Mfn2.…”
Section: Mitochondrial Dynamics and Dysfunction In Atherosclerosismentioning
confidence: 99%
“…Studies have shown that the continuous fission and fusion of mitochondria are important for maintaining mitochondrial morphology and function ( Kyriakoudi et al, 2021 ). Mammals contain two mitofusins, namely mitofusin (Mfn)-1 and Mfn2.…”
Section: Mitochondrial Dynamics and Dysfunction In Atherosclerosismentioning
confidence: 99%
“…Mitochondria are key organelles that produce cellular ATP and are also involved in the cell metabolic status, programmed cell death, calcium homeostasis, and the generation and control of reactive oxygen species (ROS) ( Wai and Langer, 2016 ). They are highly dynamic structures, which change their morphology and spatial distribution according to metabolic requirements, allowing cells to adapt to energy demands and maintain homeostasis ( Kyriakoudi et al, 2021 ). This changeable and adaptable nature, known as mitochondrial dynamics, includes both the regulation of mitochondrial architecture, mediated by the fusion and fission, and the movement of mitochondria along the cytoskeleton ( Chan, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In obesity, mitochondrial dynamics are disrupted. Mitochondrial dynamics depend on the availability of nutrients and energy consumption of cells [89] . It is known that, with nutrient deficiency and increased energy consumption, the mitochondrial network becomes elongated, while an abundant supply of nutrients and a decrease in energy requirements are associated with mitochondrial fragmentation [90] .…”
Section: Mitochondrial Dynamics In Metabolic and Some Inflammatory Di...mentioning
confidence: 99%